IMPLICATURE IN THE STUDY OF PRAGMATICS - Amrullah, Latif (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
In communication, people cannot be separated from conversations where actually there is something to be implied on. The existence of implicature, however, is hardly needed as a tool to bond the interlocuters. Implicature is divided into two, i.e. conventional implicature and conversational implicature. To understand the implicature, the instruments such as speech events, reference, cultural background and daily experience are used.